Metastatic tumors of the jejunum-ileum - Piñeyro, Alberto; Piñeyro, Alberto; Carriquiry, Luis (Cirugía del Uruguay, 2004)
Malignant tumors of sma/1 intestine are rare and in clínica/ series metastatic involvement is exceptional. In post mortem studies the frecuency increases, particular/y in cases of mela noma. Sorne consider that the sma/1 intestine has protective e/ements, which other adjacent organs, such as the stomach and co/on,lack. Case material consists of three clínica/ cases of metastasis in jejunoileum. There fol/ows a discussion of patho/ogy, clinic, diagnosis and therapy. In al/ patients carrying a primary tumor, fundamental/y mela noma ar /ung cancer, as we/1 as digestive symptoms of acute abdominal symptomato/ogy, the differential diagnosis with metastasis in the sma/1 intestine should ever by present.